Effects on the wellness state in the period of confinement due to COVID-19 in professional soccer players - Merino-Muñoz, Pablo; Pérez-Contreras, Jorge; Adasme-Maureira, Felipe; Aedo-Muñoz, Esteban (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2021)
This study aimed to find changes in the wellness state, during the confinement period due to COVID-19, in professional soccer players from the first division B of Chile. The studied sample consisted of 28 professional male soccer players aged 26 ± 6.3 years, body mass 74.2 ± 5.5 kg, and height 177 ± 0.05 cm. The degree of well-being was evaluated through a questionnaire (McLean et al., 2010) during the 2020 competitive and confinement periods. Statistically, significant differences (p <0.05) between the competitive period and the confinement period are shown in FT (t = 2.5; p = 0.0), SO (t = 2.71; p = 0.01), ES (t = 5.07; p = 0.0), EA (t = 1.82; p = 0.08), and T (t = 4.87; p = 0.0). Small TE were reflected in the variables EA and DM (d = 0.7; d = 0.4 respectively), moderate in FAT and SO (d = 1.0; d = 1.2 respectively), and very large in ES and T (d = 2.1; d = 2.0 respectively). The CP and CV between periods for the well-being variables were the following: for FAT, 11% and 11.6%, for DM, 5.3% and 13.1%; for SO, 9.3%; 7.5%, ES 11.6% and 5.9, for EA 3.9%; 5.2%, and finally for T 8.1% and 4.0% respectively. It is possible to conclude that the state of well-being in professional soccer players is altered in the period of confinement with respect to that of competition, finding significant changes in the variables FT, SO, ES, and T, which coincided with the changes from moderate to very large of these same variables, as well as the PC were larger than the CV between periods. Therefore, we could consider these changes as real, and they could be an effect attributable to the mandatory isolation.